Equilibrium, kinetics, and thermodynamic studies on the biosorption of Reactive Red 120 dye utilizing the biomass of Enterobacter sp. MMO5 - Yahuza, Salihu; Manogaran, Motharasan; Yasid, Nur Adeela; Othman, Ahmad Razi; Abd Shukor, Mohd Yunus (Malaysian Society for Molecular Biology and Biotechnology, 2024)
Biosorption using sustainable biomass such as bacteria is highly desirable due to their large surface area. Enterobacter sp. MM05 was the organism of choice for the Reactive red-120 dye biosorption. The dye sorption optimization was done using Response Surface Methodology (RSM) and One-Factor-At-Time (OFAT). Upon RSM optimization, 50 mg/L, 150 rpm, 60 min, 7.0, and 45o C were the optimum results for the concentration, agitation, time, pH, and temperature, respectively. The biosorbent was characterized using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM) analyses. Biosorption isotherms, kinetics, and thermodynamic parameters were studied using nonlinear regression. Compared to the traditional One-factor-at-a-time (OFAT) method, the adsorption rate was about 6% higher after optimization using response surface methodology via Central Composite Design (CCD). The pseudo-second-order kinetics reaction fitted the dye biosorption with the lowest AICc and highest adjR2 values. Langmuir, Freundlich, Henry, BET, Sips, Toth, Fritz-Schlunder IV, and Fritz-Schlunder V were the mathematical isotherm models with the best fit. Except for Henry, all the isotherm models tested on the RR-120 dye provided significant fitting results. Freundlich isotherm was the best after statistical analysis, having the lowest AICc value of-51.54. The thermodynamic parameters were computed using non-linear regression based on the vant Hoff plot. The enthalpy change (ΔH°) value was 52.91 kJ/mol, indicating that the reaction was endothermic. The adsorption process was spontaneous and thermodynamically feasible, as denoted by the negative values of Gibbs free energy (ΔG°) calculated at various temperatures. An increase in the degree of randomness at the solid/liquid interface was indicated by the positive entropy change (ΔS°), which is likely due to the structural changes in the bacterial biomass and Reactive Red 120 dye upon binding. This study demonstrated the potential of the bacterial biomass as a good biosorbent for dye biosorption, particularly Reactive Red 120, and offers a promising alternative for the bioremediation of textile dyes.